Knowledge and Expectations of Pregnant Women Regarding Antenatal Ultrasound in Indian Population: A Cross-Sectional Study at a Tertiary Care Center - Dr Gulab S Saroha; Dr Debasheesh S R Das; Dr Shankar Ganesh N; Dr Saikat Bhattacharjee (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Antenatal ultrasound is a vital component of modern prenatal care, assisting in fetal growth assessment, anomaly detection, and maternal reassurance. However, awareness and expectations vary considerably across Indian populations. Objectives: To assess the knowledge, attitudes, and expectations of pregnant women regarding antenatal ultrasound and identify sociodemographic factors influencing awareness. Methods: A cross-sectional study was conducted at Base Hospital, Delhi Cantonment, over 12 months among 750 pregnant women undergoing routine ultrasound. A pre-validated questionnaire assessed demographics, knowledge, expectations, and information sources. Statistical analysis was performed using chi-square tests, with p < 0.05 considered significant. Results: Of 750 participants, 62% had adequate knowledge of ultrasound purpose, 78% recognized its role in anomaly detection, and 54% knew appropriate scan timing. However, 85% expected fetal sex disclosure despite legal restrictions. Knowledge correlated significantly with education, parity, and residence (p < 0.05). Healthcare professionals were the primary information source (46%). Conclusion: Most participants demonstrated moderate awareness but persistent misconceptions. Strengthening antenatal counseling and community-based education programs can ensure informed and ethical use of obstetric ultrasound.